New perspectives on amyotrophic lateral sclerosis: the role of glial cells at the neuromuscular junction. (1st December 2016) - Arbour, Danielle; Vande Velde, Christine; Robitaille, Richard
Abstract : Normal PSC functions may be altered and contribute to ALS pathology. Understanding PSC dysfunctions may lead to a new set of therapeutic targets. Abstract: Amyotrophic lateral sclerosis (ALS) is a disease leading to the death of motor neurons (MNs). It is also recognized as a non‐cell autonomous disease where glial cells in the CNS are involved in its pathogenesis and progression. However, although denervation of neuromuscular junctions (NMJs) represents an early and major event in ALS, the importance of glial cells at this synapse receives little attention. An interesting possibility is that altered relationships between glial cells and MNs in the spinal cord in ALS may also take place at the NMJ. Perisynaptic Schwann cells (PSCs), which are glial cells at the NMJ, show great morphological and functional adaptability to ensure NMJ stability, maintenance and repair. More specifically, PSCs change their properties according to the state of innervation. Hence, abnormal changes or lack of changes can have detrimental effects on NMJs in ALS. This review will provide an overview of known and hypothesized interactions between MN nerve terminals and PSCs at NMJs during development, aging and ALS‐induced denervation. These neuron–PSC interactions may be crucial to the understanding of how degenerative changes begin and progress at NMJs in ALS, and represent a novel therapeutic target.